Penerapan Data Sintetis dalam Simulasi Kinerja Mesin Pemipil Jagung - Hendra, Hendra; Erawadi, Dedi; Leni, Desmarita (Rekayasa Material, Manufaktur dan Energi, 2023)
Corn sheller machine simulation is a process of modeling the performance of corn sheller machines in a virtual environment using software. The purpose is to predict machine performance, test and improve machine design before mass production, and minimize development cost and time. This study conducted a simulation of corn sheller machine performance comparison using real and synthetic data, by simulating the input of 1000 kg of cobbed corn mass. Synthetic data was created using linear interpolation method using data from previous testing. The evaluation results show that synthetic data can be used as input data for simulation with sufficiently accurate results. The evaluation results show a Mean Absolute Error (MAE) value of 0.20, Mean Squared Error (MSE) value of 0.12, and Root Mean Squared Error (RMSE) value of 0.34 for net and damaged corn shelling results. However, the evaluation results for fuel consumption show an MAE value of 0.09, MSE value of 0.020, and RMSE value of 0.14. The evaluation also shows that the machine RPM affects the net and damaged corn shelling results, processing time, and fuel consumption.